2015
DOI: 10.7224/1537-2073.2014-076
|View full text |Cite
|
Sign up to set email alerts
|

Medications Are Associated with Falls in People with Multiple Sclerosis

Abstract: Background: Medication use is associated with falls in many populations, but the relationship between medications and falls in people with multiple sclerosis (MS) is not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Additionally, when considering a faller as an individual with two or more falls, centrally acting muscle relaxant medications were also associated with an increased odds of being a faller. Our results are consistent with Nilsagard et al 7 who found no association between number of medications and falls in pwMS but contrast with Gunn et al 8 and Cameron et al 9 who showed this association to be significant. Notably their samples had fewer people with progressive MS.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, when considering a faller as an individual with two or more falls, centrally acting muscle relaxant medications were also associated with an increased odds of being a faller. Our results are consistent with Nilsagard et al 7 who found no association between number of medications and falls in pwMS but contrast with Gunn et al 8 and Cameron et al 9 who showed this association to be significant. Notably their samples had fewer people with progressive MS.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our prior findings in an HIV-infected population [5], women had higher rates of falls than men in the overall population, even after adjusting for additional fall risk factors. In the multivariable analyses, HIV serostatus was not indepen-dently associated with falls, suggesting that the trend towards a higher fall rate among HIV-infected participants seen in previous studies may be attributable to an increased burden of fall risk factors such as comorbidities and greater number of medications [28,29] rather than HIV itself, as indicated by the lack of independent association with HIV serostatus, current or nadir CD4 count, viral load or ART. Indeed, the strongest independent predictors of falls in all participants were symptoms of dizziness, lightheadedness and feeling off-balance, which were reported more frequently among the HIV-infected men and women.…”
Section: Discussionmentioning
confidence: 64%
“…While CAM users are more likely to perceive herbs and supplements as a natural and safe alternative to conventional medications (Salamonsen, 2015), excessive use of supplements can lead to toxicity and has been associated with serious neurologic and systemic disease (Evans et al, 2018;Kim et al, 2019). Further, polypharmacy is more common in pwMS (Frahm et al, 2019) and higher utilization of both prescription medications and supplements increase the risk of injurious falls (Cameron et al, 2015). Our study demonstrates increased use of supplements in those also using other forms of CAM.…”
Section: Discussionmentioning
confidence: 68%